PENINGKATAN KEMAMPUAN MENGEMBANGKAN GAGASAN DALAM MENULIS ILMIAH DENGAN PENDEKATAN KONTEKSTUAL BAGI MAHASISWA JURUSAN PENDIDIKAN BAHASA DAN SASTRA INDONESIA - Ribut Wahyu Eriyanti (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2009)
This study aimed to improve the idea-developing ability to write discourse through the contextual approach among students of the Indonesian Language Department of the Muhammadiyah University of Malang. This study was an action research study. The data were the teacher’s and students’ nonverbal data in the writing learning process using the contextual approach and the students’ written discourses. The data were collected through observations, documents, interviews, questionnaire, and tests, and were analyzed by means of the qualitative technique. To enhance the data trustworthiness, the method triangulation, research prolongation, and discussions with colleagues were carried out.The results show that Group VA students of the Indonesian Language Department were able to improve their idea-developing ability to write discourse through the contextual learning from cycle to cycle. This was attained through connection, exploration and discovery, implementation, teamwork, application in other contexts, and authentic assessment. The teacher employed discovery, modeling, discussion, question and answer,group learning, and reflection techniques and authentic assessment.